Using Technology in Pharmacy Education: Pharmacy Student Performance and Perspectives When Visual Aids Are Integrated Into Learning - Curley, Louise E.; Wu, Zimei; Svirskis, Darren (Frontiers in Pharmacology, 2018)
Objectives: The role of the pharmacist has evolved and continues to evolve. The traditional role of the dispenser has been replaced with a patient-centred profession. This requires integration and application of pharmaceutical knowledge and skills to solve patient therapeutic problems and advance patient care. Therefore having evidence-based teaching strategies for learning within pharmaceutical sciences is essential. New and maturing technologies enable traditional principles of pharmaceutical science to be visualised. We aimed to explore pharmacy students’ performance before and after visual aids for learning are integrated within pharmaceutical science teaching. Student’s opinions and views of the visual aids were determined. Methods: Students were taught about selected pharmaceutical science concepts at two time points; during the second teaching point, visual aids were introduced. Students’ performance was compared before and after the implementation of visual aids using pre and post-quizzes. Alongside the post-quiz an evaluation was also completed by the students; a descriptive analysis was conducted for the Likert-type responses and an in-depth thematic analysis of the student’s free-text questions was completed using an iterative process. Results: Significant differences were seen between pre and post-quiz sessions for total score and questions that mapped to the revised-Bloom’s taxonomy lower and higher categories. Student evaluation of the visual aids were positive. Interesting themes and subthemes emerged regarding the perspectives of pharmacy students to these visual aids. Students indicated visual aids made it easier to understand, compared to written or verbal explanations, and helped with the application of pharmaceutical science concepts. However a minority of students reported that the visual aids were irrelevant, or they did not understand them. Conclusion: Students had better performance after the introduction of, and favourable responses to, the visual aids. Visual aids were a beneficial tool in regards to understanding and application of complex concepts. Improvements can be made; tailoring accompanying descriptions and using more repetition.